Riociguat treatment in patients with pulmonary arterial hypertension: Final safety data from the EXPERT registry - (:unkn) unknown (My University, 2020)
OBJECTIVE: The soluble guanylate cyclase stimulator riociguat is approved for the treatment of adult patients with pulmonary arterial hypertension (PAH) and inoperable or persistent/recurrent chronic thromboembolic pulmonary hypertension following Phase 3 randomized trials. The EXPosurE Registry RiociguaT in patients with pulmonary hypertension (EXPERT) study was designed to monitor the long-term safety of riociguat in clinical practice. METHODS: EXPERT was an international, multicenter, prospective, uncontrolled, non-interventional cohort study of patients treated with riociguat. Patients were followed for at least 1 year and up to 4 years from enrollment or until 30 days after stopping riociguat treatment. Primary safety outcomes were adverse events (AEs) and serious adverse events (SAEs) coded using Medical Dictionary for Regulatory Activities preferred terms and System Organ Classes version 21.0, collected during routine clinic visits (usually every 3-6 months) and collated via case report forms. RESULTS: In total, 326 patients with PAH were included in the analysis. The most common AEs in these patients were dizziness (11.7%), right ventricular (RV)/cardiac failure (10.7%), edema/peripheral edema (10.7%), diarrhea (8.6%), dyspnea (8.0%), and cough (7.7%). The most common SAEs were RV/cardiac failure (10.1%), pneumonia (6.1%), dyspnea (4.0%), and syncope (3.4%). The exposure-adjusted rate of hemoptysis/pulmonary hemorrhage was 2.5 events per 100 patient-years. CONCLUSION: Final data from EXPERT show that in patients with PAH, the safety of riociguat in clinical practice was consistent with clinical trials, with no new safety concerns identified and a lower exposure-adjusted rate of hemoptysis/pulmonary hemorrhage than in the long-term extension of the Phase 3 trial in PAH.
Keywords: Clinical practice; Pulmonary arterial hypertension; Pulmonary hypertension; Registry; Riociguat; Safety